2013
DOI: 10.5152/jaem.2013.002
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Type of Suicide Attempt in East Turkey: Acute Zinc Phosphide Poisoning

Abstract: Objective: The purpose of this study was to predict the clinic and demographic profile of patients who attempt suicide by poisoning with zinc phosphide. Material and Methods: All cases presenting to the ED from January 1 st 2009 to April 30 th 2011 due to Acute Zinc Phosphide Poisoning were retrospectively reviewed. Results: All cases had taken the pharmaceutical product in an attempt to commit suicide. The average age of the cases was 25.4 years. Sixteen of the cases were female (76%), and five (24%) were mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…8 A study from turkey found that autopsy revealed congestion and several necrotic areas in liver. 9 There is no antidote for poisoning with metal phosphides, such as zinc phosphide. A Turkish study showed 27 % mortality and the rate of mortality was twice as high in patients with high levels of liver enzymes as compared to patients with normal liver enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…8 A study from turkey found that autopsy revealed congestion and several necrotic areas in liver. 9 There is no antidote for poisoning with metal phosphides, such as zinc phosphide. A Turkish study showed 27 % mortality and the rate of mortality was twice as high in patients with high levels of liver enzymes as compared to patients with normal liver enzyme levels.…”
Section: Discussionmentioning
confidence: 99%
“…This is just an estimate as most cases of poisoning actually go unreported, particularly in Third World countries (1). Self-poisoning has reached epidemic proportions and has become a major public health issue in parts of the developing world (2,3). Based on the limited data, it is estimated that 220,000 deaths occur worldwide annually, and majority of these deaths are intentional (4).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc phosphide is a dark-grey, crystalline compound and is a highly effective rodenticide that is commonly used in the agricultural sector by mixing with food as bait (3). Phosphides are normally found as powders or pellets, usually as zinc or aluminum phosphide (Zn 3 P 2 and AlP); calcium and magnesium phosphide salts are also available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral alımında mide asidi ile reaksiyona girerek fosfin gazına bağlı akut zehirlenmelere yol açar (1,2). Spesifik antidotunun olmaması ve yüksek mortalitesi nedeniyle bu tür zehirlenmeler yoğun bakım ünitesinde takip edilmelidir (3).…”
Section: Introductionunclassified